Photoactivatable Aptamer-Based Biosensors for Point-of-Care Testing: Advances and Applications - Siyuan Wang; Xinyun Cui; Zixuan Zhong; Jingjing Zhang (Biosensors)
Photoactivatable aptamer sensing technology is widely used in various detection fields due to its precise spatiotemporal regulation ability, flexible material compatibility, and excellent detection performance. By introducing an optical response mechanism to regulate the efficient recognition of the target by the sensor, this strategy further broadens the regulation means of the aptamer. The application of photoactivated aptamer biosensors in point-of-care testing (POCT) can significantly improve the selectivity, sensitivity, and dynamic response ability of the POCT system. This review systematically explores the design principle and regulation mechanism of photoactivatable aptamers, with a focus on reviewing the application progress of them in the POCT platform. In addition, the existing challenges and future development trends are also discussed. It is expected that this biosensor based on photoactivatable aptamers will continue to drive POCT towards higher sensitivity, intelligence, and scene adaptability, providing innovative tools for precision medicine and environmental health monitoring.